AKTIVITAS AMILASE, LIPASE DAN PROTEASE DARI CACING Peryonix excavatus - Ari Asnani; Puji Lestari (Universitas Jenderal Soedirman, 2009)
The ability of Peryonix excavatus to live in extremely dirty area indicates that P. excavatus secretes distinctive enzymes which might be useful for industry. Thus, this research were aimed to isolate amylase, lipase and protease from P. excavatus, and to characterize the enzymes to know the optimum temperature and pH. The isolation procedure consisted of extraction and ammonium sulphate fractionation. The results showed that crude extract and ammonium sulphate fractions of P.excavatus had amylase, lipase, and protease enzymes activities. Among the three enzymes, amylase had the highest enzymatic activity whereas lipase was the least. The optimum temperature of amylase, lipase and protease were 60, 40, and 60 oC, respectively. The optimum pH of amylase, lipase and protease were 7, 7, and 8, respectively.